MAKING OF ICT-BASED PAI LEARNING MEDIA USING THE WEBSITE FOR EDUCATIONAL LEVEL STUDENTS - MAHSUS MAHSUS; KHUSNUL KHOTIMAH; AMIRUDIN AMIRUDIN (Raudhah - Proud To Be Professional, 2022)
Abstract. In the world of adult education entering the digital era, where the learning process is recommended to reduce traditional learning methods such as lectures and switch to using digital media following the rapid development of the times. In relation to the function of learning media in the world of education, several things can be emphasized, namely as a tool to make learning more effective, accelerate the learning process, improve the quality of teaching and learning processes or activities, and make it easier for educators to provide and deliver learning materials to students. This article aims at making products in the form of learning media by utilizing the development of the digital era through website media on ICT-based Islamic Education subjects for students. Here it is explained how to make a website in the form of wordpress easily for teachers to pour material so that students can also easily access learning materials using the internet network. And also how to process a post on the website for Islamic Religious Education learning materials. The post uses pictures and videos that can attract students to be more enthusiastic about learning.